2012
DOI: 10.2741/4075
|View full text |Cite
|
Sign up to set email alerts
|

The role of melatonin treatment in chronic kidney disease

Abstract: The pineal hormone melatonin plays a major role in circadian sleep-wake rhythm. Patients with Chronic Kidney Disease (CKD), especially those who are on hemodialysis, frequently suffer from sleep disturbances. In this review an overview is given of the classification of stages of chronic kidney disease, followed by a presentation of the circadian rhythm disorders in renal disease involving sleep disturbances in relation to melatonin deficiency. The therapeutic benefit of melatonin treatment in sleep disorders r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 73 publications
(79 reference statements)
0
35
1
4
Order By: Relevance
“…The present study found sleep disorders in 100 % of patients with CRF, which is a higher incidence than in control subjects matched for age and sex (approximately 32 %) and is higher than previously reported prevalences of sleep disturbance in CRF patients, which have ranged from 50 to 80 % [15,16]. This high prevalence emphasizes the gravity of this complication of CRF as sleep quality impacts the vitality and morbidity and is crucial to the overall health of these patients [15,17,18].…”
Section: Discussioncontrasting
confidence: 72%
“…The present study found sleep disorders in 100 % of patients with CRF, which is a higher incidence than in control subjects matched for age and sex (approximately 32 %) and is higher than previously reported prevalences of sleep disturbance in CRF patients, which have ranged from 50 to 80 % [15,16]. This high prevalence emphasizes the gravity of this complication of CRF as sleep quality impacts the vitality and morbidity and is crucial to the overall health of these patients [15,17,18].…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, normal daily melatonin profiles may contribute to sleep problems but not necessarily determine them, and their functional significance is unclear (Macchi & Bruce, 2004). Based on the overview of possible mechanisms of desynchronisation of sleep-wake rhythms, leading to sleep disturbances in dialysis patients (Parker, 2003) and in patients with chronic kidney disease (Russcher et al, 2012), we assume similar mechanisms for RTx recipients. The only significant finding in the intervention group after bright light therapy, applied each morning to regularise nocturnal sleep, was a phase advance in both get-up time and bedtime in the actimetry data (Burkhalter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin or its derivative has been reported to exert various biological activities like anti-oxidative6789, anti-inflammatory10111213 and anti-apoptotic141516 effects. Recently, melatonin is widely used to protect organs against endogenous damage due to its lack of toxicity.…”
mentioning
confidence: 99%